To determine if \( x = -3 \) squared is a solution to the quadratic equation \( -3x - 9x = 0 \), we first simplify the equation:
\[ -3x - 9x = -12x \]
Thus, we can rewrite the equation as:
\[ -12x = 0 \]
Next, we can solve for \( x \):
\[ x = 0 \]
Now, let's evaluate if \( x = -3 \) squared is a solution. First, we need to calculate \( (-3)^2 \):
\[ (-3)^2 = 9 \]
Now we check if \( x = 9 \) is a solution to the equation \( -12x = 0 \).
Substituting \( x = 9 \) into the equation:
\[ -12(9) = -108 \neq 0 \]
Since \( -108 \) does not equal \( 0 \), \( x = 9 \) is not a solution to the equation \( -12x = 0 \).
Thus, \( x = -3 \) squared is not a solution to the quadratic equation \( -3x - 9x = 0 \).